1963
DOI: 10.1677/joe.0.0260307
|View full text |Cite
|
Sign up to set email alerts
|

Ovulation in the Rabbit: The Time of Follicular Rupture and Expulsion of the Eggs, in Relation to Injection of Luteinizing Hormone

Abstract: Fifty-five mature oestrous does were injected intravenously with luteinizing hormone (LH) and subsequently killed between 9 hr. 52 min. and 14 hr. 30 min. after injection. At autopsy the number of freshly ruptured follicles was counted and was expressed as a percentage of the total number of follicles (ruptured and unruptured) counted, that had undergone pre-ovulatory swelling. This method of calculating 'percentage ovulation' gave results which agreed very closely with previously reported data. The calculatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

1966
1966
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 10 publications
1
35
0
Order By: Relevance
“…Rabbits were then sacrificed 10-12 hours, 1-2-7-14-17 days after hCG injection. Ovulation was assumed to occur about 10-12 hours after hCG administration [52]. Reflex ovulation was induced in other rabbits by mating.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…Rabbits were then sacrificed 10-12 hours, 1-2-7-14-17 days after hCG injection. Ovulation was assumed to occur about 10-12 hours after hCG administration [52]. Reflex ovulation was induced in other rabbits by mating.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…Ovulation or superovulation in rabbits has been induced by a variety of pre¬ parations containing gonadotrophins (Pincus, 1940;Parkes, 1943;Warwick, Murphree, Casida & Meyer, 1943;Adams, 1956;Beatty, 1958;Hafez, 1961;Harper, 1963;Kennelly & Foote, 1965). Many of these vary considerably in potency and a wide range of dosages has been employed.…”
Section: Introductionmentioning
confidence: 99%
“…A second objective was to compare cleavage stages in fertilized ova collected from FSH-primed and control rabbits at corresponding intervals after lh injection, since the work of Kennelly & Foote (1965) suggested that ovulation may be somewhat prolonged in superovulated animals when compared with those ovulated normally (Harper, 1963 Immediately after the administration of lh does were inseminated with 0T ml of high quality semen collected from fertile bucks. The semen samples were divided and used randomly across all treatment groups.…”
Section: Introductionmentioning
confidence: 99%
“…hours later (Harper 1963). All does were caged separately for at least four weeks before mating to eliminate pseudopregnant animals.…”
mentioning
confidence: 99%